Brinquedos e cultura: o universo lúdico na contemporaneidade - Pavone, Sandra (2006)
This dissertation aims at inquiring about the mazy net of relationships between toys and culture, and presents some of the social and cultural changes from medieval to postmodern society, emphasizing how the cultural traces of each age, of each social and historical context, are revealed through toys. We departed from Johan Huizinga, who connects the concept of playful to that of culture, regarding games as the very essence of other cultural manifestations. Walter Benjamin and Philippe Ariès point out some elements of the history of toys, and make an analysis of the relationship between toys, childhood and the existing social and historical context. As objects of a given culture, toys get hold of and transmit certain values, ideologies, ideas and expectations from the social field to childhood. As it plays, the child gets hold of such meanings and representations, but it also changes them. Playing is then the basic tools allowing the connection between the child and its world. In this connection between an object from a culture toys and the constitution of a given subject, which is approached through playing in childhood, we detect the possibility of opening a fertile dialogue between psychoanalysis and semiotics. Based on the contributions of Iuri Lotman s Semiotics of Culture, we considered toys as a complete text in a broader semiotic system, which the author calls semiosphere. Playing, the basic tool for the appropriation by the child of the symbolical elements of a given culture, was approached through the conceptual and psychoanalytical basis to be found in Sigmund Freud, D.W. Winnicott and Jacques Lacan. But our subsidies to the psychoanalytical field aimed at what was called psychoanalysis in expansion , that is, a shifting from the field of psychoanalytical analysis to an analysis of cultural formations, in an operation that is closer to social criticism. We finally went further into our research through the investigation of the relationship between some social and cultural paradigms and formations of post-modernity and certain forms assumed by toys and plays in the contemporary universe. Through the analysis of semiotic processes of toys and the psychoanalytical methodology, we proposed a reading and an interpretation of the subject s positions the child in this case - , and the social bound before such new meanings and social and cultural transformations. In an intersection between philosophy and psycho-analysis, we looked for a basis in Slavoj Zizek s concept of multiculturalism, in Vladimir Sfatle, which analyzes the shifting of modern productive society to post-modern consuming society, as well as in Renata Salecl, who points to the new forms of the Other at this triumphing moment of late capitalism